Integrated multi-omics analysis reveals complement component 3 as a central driver of immune dysregulation in polycystic ovary syndrome - Zhao, Xuanpeng; Meng, Qingyan; Liu, Shuang; Cheng, Linqi; Li, Baoshan; Cheng, Dongkai (Frontiers in Endocrinology, 2025)
BackgroundPolycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder with a complex pathophysiology, affecting various aspects of women’s health. Despite its widespread impact, the molecular basis and immunological aspects of PCOS remain insufficiently understood, limiting effective diagnosis and treatment strategies.ObjectiveThis study aims to elucidate the molecular and immunological landscape of PCOS by integrating gene expression profiles from healthy and PCOS-affected ovaries using both bulk and single-cell omics data, with the goal of constructing a comprehensive bioinformatics network that identifies potential biomarkers and therapeutic targets.MethodsLeveraging publicly available omics datasets, we compared gene expression between healthy ovaries and those affected by PCOS through both bulk and single-cell analyses. Our approach focused on differential gene expression analysis, identification of distinct cell types and gene signatures in PCOS, construction of disease-specific gene expression modules, and mapping of cellular differentiation trajectories. Additionally, we examined the alterations in the immune microenvironment within PCOS to identify immune-related changes.ResultsOur analyses uncovered unique molecular signatures and immune modules in PCOS, characterized by differential gene expression, the presence of unique cell types, and altered pathways compared to healthy controls. Notably, we identified a significant role for Complement Component 3 (C3) in mediating these changes. Through gene intervention targeting C3 in granulosa cells and functional studies examining the effects of secreted C3 protein on H295R cells, Low level C3 mitigated inflammatory responses, while excess C3 proved detrimental to cell growth.ConclusionOur integrative omics analysis provides new insights into the molecular and immunological underpinnings of PCOS, highlighting the role of C3 in the disease’s pathogenesis. The identification of key molecular signatures and immune modules, including the involvement of C3, opens promising avenues for the development of novel diagnostic and therapeutic strategies for PCOS. These observations suggest that modulating C3 levels could have therapeutic implications for managing PCOS.